Effects of the Implementation of an Emergency Surgical Pattern in Patients with Rhegmatogenous Retinal Detachment: A Retrospective Observational Study - Ziye Chen; Kai Gao; Kunbei Lai; Wenbin Zheng; Jizhu Li; Yaping Liu; Baoyi Liu; Xiaoyue Wei; Yuan Ma; Zitong Chen; Rebiya Tuxun; Tao Li (Journal of Ophthalmology)
Background. To analyze the effects of the implementation of emergency surgical patterns in patients with rhegmatogenous retinal detachment (RRD) and provide evidence for promoting emergency surgical patterns for RRD. Methods. We reviewed the electronic medical records of 346 patients (348 eyes) who underwent surgical repair of RRD at the Zhongshan Ophthalmic Center in Southern China. A total of 140 patients (140 eyes) in the routine inpatient surgery group were collected at the fundus disease department between January 2019 and December 2019, and 206 patients (208 eyes) in the emergency surgery group were collected at the ophthalmic emergency department between January 2021 and December 2021. Demographics, best-corrected visual acuity (BCVA) expressed as the logarithm of the minimum angle of resolution (logMAR), the status of the macula before surgery, time to presentation, treatment interval, and postoperative BCVA measured at least three months follow-up were compared. Results. The preoperative BCVA (logMAR) of the emergency surgery group and the inpatient surgery group were 1.0 (0.4–1.7) and 1.4 (0.7–1.7), respectively, with significant differences between groups (P<0.001). However, patients had a shorter time to presentation (7 days vs. 21 days, P<0.001), shorter treatment interval (2 days vs. 12 days, P<0.01), and significantly better postoperative BCVA (logMAR 0.5 vs. logMAR 1.0, P<0.001) in the emergency surgery group than in the inpatient surgery group. There was no significant difference in primary anatomical success between the two groups (P=0.802). The median follow-up for the emergency surgery group and the inpatient surgery group were 6.08 months and 6.2 months, respectively, with no significant differences (P>0.05). Conclusions. Patients who underwent emergency surgical patterns of RRD had better visual outcomes after surgery than patients with routine inpatient surgery, which might be attributed to a shorter duration, shorter treatment interval, and the preoperative status of the macula in the emergency surgery pattern. Emergency surgical patterns for RRD should be considered to achieve better surgical outcomes in suitable patients.